Penerapan STEM FROM HOME dengan Model PjBL untuk Meningkatkan Penguasaan Konsep dan Keterampilan Berpikir Kreatif Siswa SMP - Resmi Ningrum; Taufik Rahman; Riandi Riandi (PendIPA Journal of Science Education, 2022)
Learning from home is less effective, so teachers are required to be able to plan learning activities that are simpler, creative and effective. Project Based Learning (PjBL) is one of the learning models that recommended by the government. In order to combine contextual with project assignments, achieving 21st century skills is carried out through the implementation of the PjBL model with a STEM (Science, Technology, Engineering and Math) approach that is carried out at home. This study aimed to obtain information on the application of STEM from home with the PjBL model to mastery of concepts and creative thinking skills. This study used an experimental method without using a control group (Pre-Experimental) with a "One Group Pretest-Posttest Design" design by analyzing N-gain based on differences in learning outcomes before learning (pretest) and after learning (posttest). The research participants were 30, seventh grade junior high school students. Mastery of concepts and creative thinking skills as a result of implementation through STEM from home was measured by instruments in the form of a multiple choice test with 15 questions and an essay with 5 questions. The research was conducted in three times online meetings. The results showed that the application of STEM from home with the PjBL model obtained the N-gain value of students with a high category of 43% in mastery of concepts. Meanwhile, on the ability to think creatively, the N-gain value of students in the medium category was 63%. Thus the application of STEM from home with the PjBL model could improve students' mastery of concepts and creative thinking skills.